Evaluating Factors Influencing University Students’ Satisfaction and Continued Use of Health Smartwatches in Chengdu - Yang, Fan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study aims to identify the key factors influencing university students’ satisfaction and continued use of health smartwatches in Chengdu Factors evaluated in the study include perceived ease of use, perceived usefulness, enjoyment, AI user experience, AI trust, satisfaction, and continuance intention. Research design, data and methodology: The researchers employed quantitative techniques (n = 500) to conduct a questionnaire survey among undergraduate students at Chengdu Medical College. The sample was selected using non-probability sampling methods, including judgmental sampling, quota sampling, and convenience sampling. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were used to analyze the data and test the proposed research hypotheses. Results: The analysis shows that perceived usefulness, enjoyment, AI experience, and AI trust significantly influence student satisfaction in using smartwatches. Additionally, perceived usefulness is statistically proven to be driven by perceived ease of use. Student satisfaction, in turn, influences continued use of health smartwatches. Conclusions: The statistics support the six research hypotheses proposed. Thus, it is recommended to optimize the ease of use of smartwatches by enhancing their functionality for greater user-friendliness. Additionally, incorporating more accurate monitoring data and enhancing online protection can promote satisfaction and continued use.